Analisis Pengaruh Tax Avoidance Terhadap Nilai Perusahaan Berdasarkan Literature Review yang Terindeks Sinta Tahun 2014-2024 - Asterina Indah Mufliha; Indriyani Astuti Nurachman; Fitriana Fitriana; Rachmat Agus Santoso (EKOMA : Jurnal Ekonomi, Manajemen, Akuntansi, 2024)
One way for management to maximize company value is by adjusting the tax costs paid by the company. For the State, taxes are a source of funding for government administration. Meanwhile, for companies, taxation is a burden that will reduce company profits. This has an impact on companies that are trying to reduce the tax burden paid both legally and illegally. This research aims to find out how much influence tax avoidance has on company value by reviewing literature related to the impact of tax avoidance practices on company value. Through analysis of data sourced from 15 articles indexed by Sinta for 2014-2024 which contain in-depth insights into how tax avoidance strategies can influence perceptions of company value in the context of the modern economy. This research uses a descriptive qualitative literature review method using a literature review. The results of the research show that the Tax Avoidance variable is dominantly used by previous research in articles with scientific source disciplines from economics on company value.